THE EFFECTIVENESS OF USING FLASH ANIMATION AS AN ALTERNATIVE MEDIA IN TEACHING SPOKEN REPORT OF COMPUTER ENGINEERING STUDENTS AT POLYTECHNIC OF HARAPAN BERSAMA TEGAL - Dani Fitria Brilianti (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2017)
This research mainly aims at determining the effectiveness of using flash animation as alternative media in teaching spoken recount. In order to achieve the objective of the study, I designed a classroom research which was done from 2th October till 13th October 2017. There were nine meetings in this study including pre test and post test. The population is the third semester of computer engineering of computer engineering students at Polytechnic of Harapan Bersama Tegal. The numbers of the population are 21 students that consist of 10 male and 11 female students. The instrument used to obtain the data were flash animations, lesson plan, test, and questionnaire. In doing the analysis of the data, I used criterion assessment written by Harris (1969:84) to score the students’ speaking performance. The result of the study showed that the speaking achievement of the third semester of computer engineering of computer engineering students at Polytechnic of Harapan Bersama Tegal improved. The mean of the student speaking score of the pre-test was 44.76, the cycle 1 test’s result was 66.10, and the mean of the cycle 2 test was 80.00. The improvement between pre-test and the cycle 1 test was 21.32 points, the different result of cycle 1 test and the cycle 2 test was 13.10 points and the different result between pre-test and cycle 2 post test was 35.24 points. In line with the result, flash animation seems to be alternative media to improve students’ ability in performing spoken recount. Key words: Flash animation, Recount text, Speaking